Pengaruh Kecukupan Modal Terhadap Stabilitas Keuangan Bank Perkreditan Rakyat - Rustendi, Tedi (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. This study aims to determine the influence of capital adequacy on financial stability of rural banks. The capital adequacy variable is measured using CAR, while the bank financial stability variable is individually measured using Z-index. Based on secondary data from OJK and BI in the span of 4 years from sample of size 11 rural banks which are included in the non-systemic category with capital under IDR 50 billion, the results show that rural banks generally have a level of capital adequacy in the healthy category with a positive capital buffer, while the bank financial stability is generally at a sufficient level. The results of hypothesis testing using Kendall-Æ® at the 5% significant level indicate that there is concordant between capital adequacy and bank financial stability, where capital adequacy has a positive and significant effect on financial stability of rural banks.Keywords. CAR; Rural bank; Z-index.Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh kecukupan modal terhadap stabilitas keuangan BPR. Variabel kecukupan modal diukur menggunakan CAR, sedangkan variabel stabilitas keuangan bank secara individual diukur menggunakan Z-index. Berdasarkan data sekunder dari OJK dan BI pada rentang waktu 4 tahun dari sampel yang berukuran 11 BPR yang termasuk kategori non-sistemik dengan modal dibawah IDR 50 milyar, diperoleh hasil bahwa umumnya BPR memiliki tingkat kecukupan modal dalam kategori sehat dengan capital buffer positif, sementara tingkat stabilitas keuangan bank umumnya berada pada level cukup. Hasil pengujian hipotesis menggunakan Kendall-Æ® pada taraf nyata 5% menunjukkan terdapat kesesuaian (concordant) antara kecukupan modal dengan stabilitas keuangan bank, dimana kecukupan modal berpengaruh positif dan signifikan terhadap stabilitas keuangan BPR.